2019
DOI: 10.1016/j.cej.2019.03.284
|View full text |Cite
|
Sign up to set email alerts
|

Novel and versatile TiO2 thin films on PET for photocatalytic removal of contaminants of emerging concern from water

Abstract: The current work presents new and versatile photocatalytic surfaces designed to remove contaminants of emerging concerns (CECs) from water. Photocatalytic thin films of titanium dioxide (TiO2) were deposited on a polyethylene terephthalate (PET) surface (PET-TiO2) and photosensitized by a natural and non-hazardous curcumin (turmeric). The nanocrystalline TiO2 thin film was deposited in a single stage and solvent-free process, without thermal post treatment, using the high power impulse magnetron sputtering (Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 73 publications
1
8
0
1
Order By: Relevance
“…However, one of the challenges to produce these filter media is the adjustment and control of several parameters which influence fiber production, (explored in this work) [ 38 , 39 , 40 , 41 , 42 ]. Thus, the utilization of this technique to produce filter media from post-consumer PET bottles is a very promising and ecologically sustainable alternative because it highly contributes to the reduction of environmental pollution [ 6 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the challenges to produce these filter media is the adjustment and control of several parameters which influence fiber production, (explored in this work) [ 38 , 39 , 40 , 41 , 42 ]. Thus, the utilization of this technique to produce filter media from post-consumer PET bottles is a very promising and ecologically sustainable alternative because it highly contributes to the reduction of environmental pollution [ 6 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has become an excellent heterogeneous photocatalyst because of its low cost, nontoxicity, mechanical robustness, and chemical resistance . Suspended TiO 2 nanoparticles are supposed to be the commonest application form as suspended slurries because vigorously mixing can maximally enhance mass transfer and light utilization, but such application is seriously limited by weak recyclability and extra energy cost and the possibility of accidentally discharging nanoparticles. , Alternatively, membranes modified with photocatalytic nanoparticles have shown their potential to address the aforementioned problems . A suitable membrane loaded with TiO 2 can adsorb and bring contaminants close to photocatalytic sites for utilizing the short-lived unselective reactive radicals more efficiently …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Alternatively, membranes modified with photocatalytic nanoparticles have shown their potential to address the aforementioned problems. 16 A suitable membrane loaded with TiO 2 can adsorb and bring contaminants close to photocatalytic sites for utilizing the short-lived unselective reactive radicals more efficiently. 17 Compared to other membranes, electrospun nanofibrous membranes (NFMs) with selective superwettability have been considered as prominent photocatalytic substrates because of their high porosity, easily tunable structures, large specific area, three-dimensional networks with good connectivity, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Marcelino et al 95 reported on the good photocatalytic activity of TiO 2 sputtered on polyethylene terephthalate (PET) in the removal of contaminants of emerging concern, specifically for the fungicide carbendazim (CBZ) and anthropogenic pollution tracer caffeine (CAF) up to 39% under a combination of UV and visible light irradiation. It is stated that TiO 2 was successfully deposited onto the PET flat sheet surface by using the high power impulse magnetron sputtering (HiPIMS) technique.…”
Section: Photocatalyst Immobilization Methodsmentioning
confidence: 99%